PENGARUH PEMBERIAN DECANTER SOLID DAN JUMLAH BENIH PERLUBANG TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L) DI MEDIA TANAH ULTISOL - Markus Iwan Purwono; Bambang F Langai; Jumar Jumar (Universitas Lambung Mangkurat, 2021)
A study entitled The Effect of Giving Solids Decanter and the Number of Perforated Planting Seeds on Growth and Yield of Corn Plants (Zea Mays L) in Ultisol Soil. This research was conducted for four months and was carried out in the Galuh Merindu 1 residential land and the Biology Laboratory of the Faculty of Agriculture, University of Lambungmangkurat. This study uses an environmental design in the form of a Completely Randomized Design using the interaction of two experimental factors, namely the dose of a solid decanter and the number of seeds per planting hole, which consists of seven treatments, namely: S0 (Control), S1 (10 ton/ha decanter solid), S2 (20 ton/ha decanter solid), S3 (30 ton/ha decanter solid), J1 (1 corn seed varieties BISI 18), J2 (2 corn seed varieties BISI 18). J3 ( 3 corn seed varieties BISI 18). Repeated three times so that there are 36 units of experiments, and from each unit of experiment consists of two polybags so that there are 72 plant polybags. Observations were made in the form of: plant height, number of leaves, plant wet weight, plant dry weight, length of crop cobs, diameter of planting cobs, number of row of perongkol seeds, number of seeds per row of cob, weight of 100 dried shelled seeds, dried shelled yield. The results of this study showed the best number of seeds treated at 1 seed per planting hole (J1), the best solid decanter treatment occurred at 30 tons / ha (S3) treatment and the best interaction was on the treatment of 1 seed per planting hole with 30 tons / ha Solid Decanter (J1S3).